2003
DOI: 10.1074/jbc.m212194200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine Is Regulated by Phospholipid Methylation

Abstract: Mild hyperhomocysteinemia is an independent risk factor for cardiovascular disease. Homocysteine, a nonprotein amino acid, is formed from S-adenosylhomocysteine and partially secreted into plasma. A potential source for homocysteine is methylation of the lipid phosphatidylethanolamine to phosphatidylcholine by phosphatidylethanolamine N-methyltransferase in the liver. We show that mice that lack phosphatidylethanolamine N-methyltransferase have plasma levels of homocysteine that are ϳ50% of those in wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 32 publications
(29 reference statements)
4
90
1
1
Order By: Relevance
“…Moreover, hepatocytes isolated from Pemt Ϫ/Ϫ mice secreted less Hcy into the medium than did hepatocytes from littermate controls. Because PEMT deficiency does not change the levels of enzymes involved in metabolizing Hcy and because the levels of hepatic AdoMet and AdoHcy were unaltered, we concluded that PEMT activity directly regulates plasma Hcy levels (45).…”
Section: Pemt and Homocysteinementioning
confidence: 87%
See 2 more Smart Citations
“…Moreover, hepatocytes isolated from Pemt Ϫ/Ϫ mice secreted less Hcy into the medium than did hepatocytes from littermate controls. Because PEMT deficiency does not change the levels of enzymes involved in metabolizing Hcy and because the levels of hepatic AdoMet and AdoHcy were unaltered, we concluded that PEMT activity directly regulates plasma Hcy levels (45).…”
Section: Pemt and Homocysteinementioning
confidence: 87%
“…Reconstitution of PEMT activity in McArdle cells stimulated Hcy secretion into the medium compared with vector-transfected cells (45). Mutagenesis of lysine 197 in the C-terminal ER retrieval motif of PEMT resulted in re-localization of PEMT from the ER to the Golgi.…”
Section: Pemt and Homocysteinementioning
confidence: 94%
See 1 more Smart Citation
“…According to Preynat et al [2010], folic acid per se or together with vitamin B 12 shows a tendency towards increasing the ratio of phosphatidylcholine (PC) to phosphatidylethanolamine (PE) [Preynat et al, 2010]. About 50% of the plasma Hcy is involved in PC synthesis in the liver [Noga et al, 2003]; therefore, PC synthesis is recognized as a contact point between SAM and phospholipid metabolisms [Obeid & Herrmann, 2009]. …”
Section: Triglyceridesmentioning
confidence: 99%
“…Entretanto, tais dados não podem ser fielmente reproduzidos em humanos. Ainda assim, autores apontam algumas controvérsias quanto aos clássicos estudos realizados por Mudd e Pole 36 e Mudd et al 37 e sugerem que a síntese de creatina pode não ser a maior responsável pelas reações de metiltransferases, apontando a biossíntese de fosfatidilcolina como importante determinante da demanda de metilação e consequentemente significante na produção de Hcy 56 . Além disso, estudos recentes têm demonstrado que outras importantes substân-cias podem modular o balanço de metilação e os ní-veis de Hcy como a betaína, glicina e serina 10,11 .…”
Section: -Conclusões E Perspectivasunclassified